2022
DOI: 10.1093/ibd/izac022
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed-methods Assessment of the Impact of Insurance Issues on the Emotional and Physical Health of Patients With Inflammatory Bowel Disease

Abstract: Background In patients with inflammatory bowel disease (IBD), failure to adhere to treatment regimens due to insurance issues can lead to disease complications. Our aim was to examine patients’ perceptions of the impact of insurance issues on their health. Methods Twenty-nine patients with IBD at a large US academic center and an insurance issue participated in a mixed-methods study. Retrospective chart review and an online q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In the past, qualitative studies, such as questionnaire surveys and semistructured interviews, were used for patients with Crohn’s disease [ 5 , 6 ]. One qualitative study explored the experience of twenty-five participants with IBD and moderate-to-severe symptoms and suggested that psychotherapists working with IBD need advanced skills to gain a clear understanding of the different processes impacting patients’ mood and levels of anxiety [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the past, qualitative studies, such as questionnaire surveys and semistructured interviews, were used for patients with Crohn’s disease [ 5 , 6 ]. One qualitative study explored the experience of twenty-five participants with IBD and moderate-to-severe symptoms and suggested that psychotherapists working with IBD need advanced skills to gain a clear understanding of the different processes impacting patients’ mood and levels of anxiety [ 6 ].…”
Section: Introductionmentioning
confidence: 99%